Financial Performance Analysis in Predicting Profit Growth at PT. Kalbe Farma Tbk - Sri wahdini; Alwi; Aris Munandar (JEKAMI Journal of Accounting, 2024)
Financial performance is a key indicator of a company's health and an essential tool for predicting future profit growth, which aids in investment decisions. This study aims to analyze the influence of the financial ratios Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on profit growth at PT. Kalbe Farma Tbk. Utilizing a quantitative approach, the study employs various analytical tools such as normality test, autocorrelation test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation and determination analysis, T test, and F test. The data analyzed includes financial reports from PT. Kalbe Farma Tbk for the years 2013-2022. The findings reveal that DER has no significant effect on profit growth, while NPM has a significant positive effect. This implies that while the amount of debt relative to equity does not influence profit growth, the company's ability to manage its expenses relative to sales significantly enhances its profit growth prospects. The results underscore the importance of profitability ratios in financial performance assessments and investment decisions. This study contributes to the understanding of financial health indicators in the pharmaceutical industry, particularly in the context of an established company like PT. Kalbe Farma Tbk, and provides insights for investors and financial analysts in evaluating investment opportunities based on financial performance metrics.